Evidence based clinical practice guideline for follow-up care in persons with spinal cord injury - Eriks-Hoogland, Inge; Müller, Lorena; Baumberger, Michael; Huber, Burkhart; Michel, Franz; Belfrage, Celina; Elmerghini, Hicham; Veseli-Abazi, Mide; Böthig, Ralf; Fiebag, Kai; Thietje, Roland; Jordan, Xavier (Frontiers in Rehabilitation Sciences, 2024)
IntroductionWhile it is well-established that follow-up care programs play a crucial role in preventing and early detecting secondary health conditions (SHCs) in persons with spinal cord injury [SCI, including spina bifida (SB)], the availability of evidence-based follow-up care programs remains limited. Under the leadership of the German-speaking Medical Society for Paraplegiology (DMGP), we have developed an evidence based clinical practice guideline for follow-up care of SHCs in persons with SCI and identify research gaps.MethodsThis guideline was developed in accordance with the regulations of the Association of the Scientific Medical Societies in Germany (AWMF e.V.). To ensure an evidence-based guidance, we utilized the International Classification of Functioning, Disability and Health (ICF) generic core set and ICF Core Set for individuals with SCI in long-term context as our foundational framework. We conducted a comprehensive literature review to identify existing recommendations for follow-up care and graded the level of evidence according to relevant instruments. Subsequently, we formulated recommendations and achieved consensus through a structured nominal group process involving defined steps and neutral moderation, while adhering to the criteria outlined in the German guideline development instrument (DELBI).ResultsAlthough there is a fair number of literatures describing prevalence and severity of SHCs after SCI, the amount of literature including recommendations was low (19 for SCI and 6 for SB). Based on the current evidence on prevalence and severity of SHCs and available recommendations, a clinical practice guideline on follow-up care of most relevant SHCs was defined. The recommendations for follow-up care are described in the following chapters: (1) Nervous system; (2) (Neuropathic) pain; (3) Cardiovascular diseases; (4) Respiratory System; (5) Immunological system, vaccination and allergies; (6) Gastrointestinal tract and function; (7) Endocrinological system and nutrition; (8) Urogenital system; (9) Contraception, pregnancy, birth and postpartum care; (10) Musculoskeletal system; (11) Pressure injuries; (12) Psychological health; (13) Medication and polypharmacy.ConclusionWe could successfully establish an evidence based clinical practice guideline for follow-up care of SHCs in individuals with SCI. There is however a notable lack of high-quality recommendations for SCI follow-up care.